The Role of The Cytomegalovirus Antigenemia Assay in the Detection and Prevention of Cytomegalovirus Syndrome and Disease in Solid Organ Transplant Recipients: A Review of the British Columbia Experience - Erica D Greanya; Nilufar Partovi; Eric M Yoshida; R Jean Shapiro; Robert D Levy; Chris H Sherlock; Gwen M Stephens (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The pp65 cytomegalovirus (CMV) antigenemia assay has been used as a means of guiding the pre-emptive therapy of CMV disease in solid organ transplant (SOT) recipients. Recently, concerns have been raised regarding the utility of the test to accurately and precisely detect viral activity early enough to reduce the morbidity and mortality associated with CMV.